Fatty acids (Ministry of Agriculture, Fisheries and Food, 1998)
Presents authoritative data on up to 37 individual fatty acids, including geometric and positional isomers, for over 500 foods compiled by the Ministry of Agriculture, Fisheries and Food, from analyses commissioned as part of the Ministry\'s nutrient surveillance programme. Softcover.
McCance and Widdowson's the composition of foods ; Suppl. 7
Keywords: zemědělství a potravinářství; fyziologie výživy; Food; potraviny; nutriční terapie, dietoterapie a výživa; Nutritional Physiological Phenomena